Incorporating vertical collaboration to address sustainable development goals: the Monarch Route Project - Cuevas-Cancino, Maria de la O; Peña-Becerril, Maritza; Mondragon-Estrada, Enrique; Camacho-Zuñiga, Claudia (Frontiers in Education, 2024)
Higher Education Institutions in their societal transformative role need to effectively integrate the UN's Sustainable Development Goals (SDGs) and the 2030 Agenda into their curricula. Our goal is to inspire and trigger the discussion among the academic community on learning environments for education for sustainable development. We report The Monarch Route (MRP), a project conducted at Tecnologico de Monterrey and awarded with the 2018 Premios Latinoamerica Verde. Engaging all the students enrolled in the different semesters of the Sustainable Development Engineering (SDE) program, it adopted a research-based learning methodology highly flexible at setting the final deliverables and due dates. It also implemented horizontal (intraclass), vertical (interclass), and interdisciplinary (multiple courses) student collaboration. In partnership with a non-governmental organization, the MRP aimed to reverse the extinction threat to the monarch butterfly while benefiting rural communities along the butterfly's migratory route. With an exploratory action research approach, we analyzed the data gathered two months after the end of the courses: A survey on the perceived learning outcomes (87% confidence level), and a letter for future classes sharing their experience on the MRP, both optional. The analysis included a mixed methodology, i.e. quantitative and qualitative, including text Mining; which evidenced that the participants strengthened both, transverse competences (collaboration, citizenship, communication, critical thinking), and disciplinary competences (subject matter). The MRP is innovative for its dynamic structure that resembles the interconnectedness of real professional practice, scientific research, and environmental conservation efforts. Besides the disciplinary application and societal relevance, the instructional design of MRP reflects that contributing to 2030 Agenda requires a multi-faceted approach, involving educational institutions, community partnerships and interdisciplinary collaboration. Traditional education no longer fulfills our needs to face environmental challenges; This is a provisional file, not the final typeset article academics, institutions, and governments are encouraged to implement policies and strategies to educate for a sustainable and better future for humanity and the planet.